2000
DOI: 10.1128/iai.68.12.6663-6669.2000
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Modulates Proinflammatory Cytokines in the Human Monocytic Cell Line THP-1 Stimulated withBorrelia burgdorferiLipoproteins

Abstract: We determined previously that lipoproteins of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 69 publications
6
62
1
1
Order By: Relevance
“…Exogenous TNF-␣ has been reported to augment IL-10 production in monocytes [40], and IL-10 has also been demonstrated to suppress LPS-induced IL-6 and IL-12 production [41]. We considered the possibility that enhanced production of TNF-␣ by p110␣-deficient cells might have led to augmented IL-10 production through a paracrine effect and that this may have led to suppression of IL-6 and IL-12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous TNF-␣ has been reported to augment IL-10 production in monocytes [40], and IL-10 has also been demonstrated to suppress LPS-induced IL-6 and IL-12 production [41]. We considered the possibility that enhanced production of TNF-␣ by p110␣-deficient cells might have led to augmented IL-10 production through a paracrine effect and that this may have led to suppression of IL-6 and IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…5D) production by p110␣-deficient cells to control levels. IL-10 has also been reported to suppress LPS-induced IL-6 and IL-12 production [41]. To investigate whether diminished LPS-induced IL-6 and IL-12 secretion by p110␣-deficient THP-1 cells was a result of enhanced IL-10 production, neutralizing antibody to IL-10 was added or not prior to stimulation of cell with LPS (Fig.…”
Section: Lps-induced Cytokine Production In Thp-1 Cells Is Mediated Tmentioning
confidence: 99%
“…There is evidence pointing to the importance of a T H 1/T H 2 balance, because increased IL-12 and T H 1-type cytokines are associated with disease progression in humans and susceptible strains of inbred mice (12)(13)(14)(15), whereas cytokines such as IL-10 have a beneficial effect (16)(17)(18)(19). In contrast, Bockenstedt et al (20) have shown that CD4 ϩ T H 1 cells were beneficial for the regression of carditis.…”
mentioning
confidence: 99%
“…IL-10 is known to suppress a number of different immune cell types, and its main biological role appears to involve reducing and eventually terminating inflammatory responses (61). M responses are potently suppressed by IL-10, and because M are believed to play a central role in both the innate and adaptive immune responses to B. burgdorferi, it is possible that M are better able to eradicate spirochetes in the absence of the substantial IL-10 amounts elicited in response to B. burgdorferi by B6 mice (60,62,63). Alternatively, our previous studies also showed that infected IL-10 Ϫ/Ϫ mice possessed significantly higher levels of B. burgdorferi-specific, as well as total, Ab levels compared with infected B6 mice (60), so it is possible that much of the increased clearance is mediated by this enhanced Ab response.…”
mentioning
confidence: 99%